Exosomes Play an Important Role in the Progression of Plasma Cell Mastitis via the PI3K-Akt-mTOR Signaling Pathway - Xiaohong Wang; Yong Han; Jian Liu; Yingzhe Zhang; Kai Cheng; Jiwei Guo; Qingqun Guo; Song Liu; Hongguang Sun; Yitong Hua; Guoqiang Zhang; Shujian Xu; et al. (Mediators of Inflammation)
Background. Plasma cell mastitis (PCM) is one of the most frequently encountered inflammatory diseases of the nonlactating breast. However, its pathogenesis has remained unknown. Methods. In this study, we observed the ultrastructure changes of PCM by a transmission electron microscope. The transcriptome expression difference of exosomes was detected by RNA-Seq; then, we confirmed the key difference genes by western blot and immunohistochemistry. Finally, we established the mouse PCM model by tissue homogenate injection to validate the role of exosomes on the progression of PCM. Results. The analysis of the exosomal transcriptome expression difference between PCM and normal mammary tissues using RNA-Seq showed the differential genes and enrichment pathways involved in the course of PCM. The decreased HSP90AA1 and EEF2, excessive production of p-AKT, and p-mTOR were consistent with clinical specimens. Inhibition of exosome secretion significantly inhibited inflammatory cell infiltration, and the mammary duct had maintained a better structure in the PCM mouse model. Conclusion. Our results revealed the role of exosomes acting as critical signal introduction facilitators in the progression of plasma cell mastitis and identified potential key genes in the regulation of this process. These results will help to dissect the molecular mechanism of PCM and provide therapeutic targets.